Electrospinning of palladium/silica nanofibers for catalyst applications. Issue 52 (10th June 2015) - Wen, Shipeng; Liang, Meili; Zou, Rui; Wang, Zhoujun; Yue, Dongmei; Liu, Li
<x xml:space="preserve">Abstract</x> A new inorganic supported catalyst of silica (SiO2)-supported palladium (Pd) nanofibers was successfully fabricated by the electrospinning followed by the calcination at high temperature and the reduction in H2 atmosphere.